Fabrication of Curcumin-loaded Gliadin Electrospun Nanofibrous Structures and Bioactive Properties - Akman P.K.; Bozkurt, Fatih; Balubaid M.; Yilmaz M.T. (Korean Fiber Society, 2019)
In this work, the feasibility and potential of food-grade gliadin nanofiber as a delivery vehicle for curcumin were investigated. By optimizing the electrospinning parameters, homogeneous and fine gliadin nanofibers containing different amounts of curcumin were fabricated. It was observed that gliadin micro-nanoparticles were gradually transformed to gliadin nanofibers and thicker nanofibers were obtained with the increment of the gliadin concentration. The electrospun nanofibers were characterized in terms of morphological, molecular, thermal and crystallographic properties. Nanofibers were nearly uniform with smooth surface characteristics and their average diameter ranged between 258 to 375 nm. Encapsulation efficiency of gliadin nanofibers increased with the increment of curcumin loading, which was also confirmed by X-ray diffraction patterns revealing that the most part of curcumin could be encapsulated in gliadin nanofibers. In vitro assessments of nanofibers indicated that the curcumin-loaded gliadin nanofibers showed a controlled release of curcumin and protected its free radical scavenging ability. In addition, these nanofibers showed important levels of antibacterial activities against Staphylococcus aureus and Escherichia coli. Furthermore, the encapsulation of curcumin within nanofibers conspicuously enhanced the antioxidant and antibacterial activities of curcumin within these nanofibers. The results suggested that the gliadin nanofiber could be an available carrier for the delivery of curcumin and has the potential for applications in the food industry and other bioactive delivery systems. © 2019, The Korean Fiber Society.
Keywords: Curcumin; Electrospinning; Encapsulation; Gliadin; Nanofiber